1994
DOI: 10.1111/j.1651-2227.1994.tb13400.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy requirements in sick preterm babies

Abstract: The energy requirements of healthy preterm babies are well documented in the literature. However, the clinical load in neonatal intensive care units is due to sick preterm infants requiring prolonged mechanical ventilation, many of whom will develop bronchopulmonary dysplasia. It is this group in which knowledge of energy requirements is scanty. This group also has poor energy reserves and is often intolerant of enteral and parenteral nutrition. In this article, we will review methods of measurement of energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…5 Specific neonatal morbidity (ventilator and oxygen dependent infants) may also increase metabolic demands by as much as 25% compared to controls. 6,7 The Committee on Nutrition of the American Academy of Pediatrics have recommended a caloric intake of 120 kcal/kg/ day for children enterally fed and 80 to 100 kcal/kg/day for those parenterally fed, with a protein intake of 3.5 to 4 g/kg/day. 3 However, it is difficult for most VLBW infants to reach this suggested caloric and protein intake in the first two months of age.…”
Section: Introductionmentioning
confidence: 99%
“…5 Specific neonatal morbidity (ventilator and oxygen dependent infants) may also increase metabolic demands by as much as 25% compared to controls. 6,7 The Committee on Nutrition of the American Academy of Pediatrics have recommended a caloric intake of 120 kcal/kg/ day for children enterally fed and 80 to 100 kcal/kg/day for those parenterally fed, with a protein intake of 3.5 to 4 g/kg/day. 3 However, it is difficult for most VLBW infants to reach this suggested caloric and protein intake in the first two months of age.…”
Section: Introductionmentioning
confidence: 99%
“…A baby weighing 1000 g at birth has only 2% of body weight as fat and <0.5% as glycogen compared with 15% and 1.2%, respectively, in the term infant 10. There may also be increased metabolic demands in ventilated VLBW infants, because studies in both ventilator dependent and oxygen dependent babies with BPD have shown that energy expenditure is about 25% higher than in controls 11. Undernutrition has many effects in the sick VLBW infant.…”
mentioning
confidence: 99%
“…However, we should recognize that most studies concern 'healthy' or stable preterm infants and that little is known about the metabolic impact of particular diseases, and how all this affects the needs of the infant [98][99][100][101]. Although some research has been done regarding the metabolic differences and capabilities between small-for-gestational-age and appropriate-for-gestational-age infants, this has not led to a comprehensive nutritional strategy that suits their specific demands.…”
Section: Resultsmentioning
confidence: 91%